How and Why to Define Unexplained Infertility? - Abdallah, Karim S.; Hunt, Sarah; Abdullah, Sayed A.; Mol, Ben W.J.; Youssef, Mohamed A. (Seminars in Reproductive Medicine, 2020)
Unexplained infertility represents up to 30% of all cases of infertility. It is a diagnosis of exclusion, where no cause for infertility may be identified in the investigation of the couple, be it anovulation, fallopian tube blockage, or severe male factor. Unexplained infertility therefore cannot be considered a diagnosis to which a specific treatment is directed, rather that it indicates a failure to reach a diagnosis of the true cause of infertility. In this review, we explore the evidence base and potential limitations of the current routine infertility assessment. We also aim to highlight the importance of considering the prognosis of each individual couple through the process of assessment and propose a reconsidered approach to treatment, targeted to the prognosis rather than the diagnosis. Ultimately, a better understanding of the mechanisms of infertility will reduce the number of couples diagnosed with “unexplained” infertility.
Keywords: unexplained infertility; definition; prognosis